The cell of origin and subtype of K-Ras-induced lung tumors are modified by Notch and Sox2 - Xu, Xia (Cold Spring Harbor Laboratory Press, 2014)
Cell type-specific conditional activation of oncogenic K-Ras is a powerful tool for investigating the cell of origin of adenocarcinomas in the mouse lung. Our previous studies showed that K-Ras activation with a CC10(Scgb1a1)-CreER driver leads to adenocarcinoma in a subset of alveolar type II cells and hyperplasia in the bronchioalveolar duct region. However, no tumors develop in the bronchioles, although recombination occurs throughout this region. To explore underlying mechanisms, we simultaneously modulated either Notch signaling or Sox2 levels in the CC10(+) cells along with activation of K-Ras. Inhibition of Notch strongly inhibits adenocarcinoma formation but promotes squamous hyperplasia in the alveoli. In contrast, activation of Notch leads to widespread Sox2(+), Sox9(+), and CC10(+) papillary adenocarcinomas throughout the bronchioles. Chromatin immunoprecipitation demonstrates Sox2 binding to NOTCH1 and NOTCH2 regulatory regions. In transgenic mouse models, overexpression of Sox2 leads to a significant reduction of Notch1 and Notch2 transcripts, while a 50% reduction in Sox2 leads to widespread papillary adenocarcinoma in the bronchioles. Taken together, our data demonstrate that the cell of origin of K-Ras-induced tumors in the lung depends on levels of Sox2 expression affecting Notch signaling. In addition, the subtype of tumors arising from type II cells is determined in part by Notch activation or suppression.